The Effect of Managerial Overconfidence on Firm Value: The Mediating Role of Organizational Capital and Tax Avoidance - Reyhan Herwanda; Anisa Fahmi (Management Analysis Journal, 2025)
This study aims to determine the effect of managerial overconfidence on firm value with organizational capital and tax avoidance as mediating variables. Using a quantitative approach, the study employs multiple linear regression analysis and path analysis on panel data from 69 manufacturing firms listed on the Indonesia Stock Exchange during 2021–2023. The results show that managerial overconfidence significantly reduces firm value, both directly and indirectly. Conversely, organizational capital has a significant positive effect on firm value, while tax avoidance also contributes positively, albeit with potential long-term risks. The analysis further reveals that organizational capital and tax avoidance significantly mediate the relationship between managerial overconfidence and firm value. This research contributes theoretically by extending the literature on behavioral accounting, organizational resources, and tax management. Practically, the study provides insights for regulators, auditors, and corporate governance bodies in monitoring managerial decision-making to prevent excessive risk-taking and to ensure that organizational capital investments and tax strategies enhance sustainable firm value rather than create distortions.